(untitled) (PerCursos, 2010)
O presente texto discute algumas características da lógica do capital e seu impacto no processo de inserção de jovens no mercado do trabalho. A ênfase é dada aos componentes nefastos desta lógica perversa sobre a vida social dos trabalhadores a partir da análise de um filme que retrata os limites entre sanidade e loucura no trabalho. Palavras-Chave: Trabalho. Jovem. Capital. Abstract This paper discusses some characteristics of the logic of capital and its impact in the process of the youth insertion into the labour market. The emphasis of the discussion is on the tragic parts of this perverse logic on the workers’ social life, based on the analysis of a movie that shows the limits between mental health and madness into the labour context. Keywords: Labour. Youth. Capital.